PELATIHAN PENINGKATAN KESADARAN HALAL DI KALANGAN PENGURUS KOPONTREN AL-AMIEN PRENDUAN SUMENEP MADURA - In Amir Ridho Al Fadholi; Sitti Humairoh (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
Not many people are aware of the importance of halal products. When people use a product, people often pay little attention to halalness. People's behavior when buying products is sometimes only based on orientation towards the products they like. In line with the implementation of the Halal Product Guarantee Law (RUU-JPH) Number 33, 2014, one of the articles of which states that all products must be certified halal, halal awareness of food products and other products will be raised regarding the presence or absence of non-halal components. halal is absolutely necessary. Therefore, it is very necessary to carry out outreach and training regarding halal awareness through community service programs. Community service activities followed by the KKNT program within the al-Amien Prenduan Islamic Boarding School Cooperative, Sumenep Madura have been carried out well. Even though various obstacles are still found in its implementation, this is a norm in human life. The level of success of this service activity can be seen from the enthusiasm of the Kopontren managers in participating in this activity. Furthermore, it is hoped that halal awareness and literacy levels will increase among Kopontren managers and the surrounding community who provide various food needs for students and boarding school residents, so that all food and beverage products are guaranteed to be halal by submitting them to obtain a halal certificate.